1995
DOI: 10.1007/bf00179392
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and genomic characterization of LST1: a new gene in the human TNF region

Abstract: The leucocyte specific transcript - 1 (LST1) represents the human homolog of the mouse B144 transcript, encoded within the tumor necrosis factor (TNF) region of the human major histocompatibility complex class III interval. The gene is localized about 4 kilobases upstream of the lymphotoxin beta gene. It spans a polymorphic genomic region encompassing the microsatellites TNFd and TNFe in intron 3 and a polymorphic Pvu II restriction site 260 base pairs downstream of the polyadenylation signal. Isolation of a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…It revealed that LST1/A is substantially enriched in the spleen, peripheral blood monocytes, and granulocytes, as well as the cell lines of myeloid origin, indicating that LST1/A is expressed predominantly in the leukocytes of myeloid lineage. Although this conclusion is only in partial agreement with previously published studies (1,3,(5)(6)(7)(8), we consider our results reliable for several reasons. 1) We analyzed LST1/A expression profile in primary tissues and blood subpopulations, as well as in cell lines both at the protein and the mRNA levels and obtained a set of mutually supporting data.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It revealed that LST1/A is substantially enriched in the spleen, peripheral blood monocytes, and granulocytes, as well as the cell lines of myeloid origin, indicating that LST1/A is expressed predominantly in the leukocytes of myeloid lineage. Although this conclusion is only in partial agreement with previously published studies (1,3,(5)(6)(7)(8), we consider our results reliable for several reasons. 1) We analyzed LST1/A expression profile in primary tissues and blood subpopulations, as well as in cell lines both at the protein and the mRNA levels and obtained a set of mutually supporting data.…”
Section: Discussionsupporting
confidence: 92%
“…ing results on the expression pattern of LST1 have been reported (1,3,5,7,8). Thus, we revisited this issue using a quantitative comparison of LST1/A expression levels in various cell subsets and tissues at both the mRNA and protein levels.…”
Section: Lst1/a Is Specifically Expressed In Myeloid Cells-conflict-mentioning
confidence: 97%
See 2 more Smart Citations
“…2 Polymorphism has been described in intron 3 of the LST-1 gene, including two dinucleotide repeats termed TNFd and TNFe. 3 It has been reported that variability in TNFa production is associated with alleles at the TNFd locus. A strong correlation between inheritance of the TNFd3 allele and high TNFa production by leucocytes in vitro was shown.…”
Section: Introductionmentioning
confidence: 99%